The emergence of Islamic finance: an exploratory study of Brazil - Abduni, Leila Mohamad (2018)
Islamic finance has been a trendy topic globally, gaining the attention of Muslims and non-Muslims. It stands for a financial system that follows the sharia (Islamic law), which is guided by ethical principles and social justice. The main prohibition usually linked to Islamic finance is of interest, but there is much more to it. It offers a portfolio of products and services which compete with the ones present in the conventional system, however these preserve the Islamic principles. Despite the global reach, Islamic finance did not set foot in Brazil or Latin America overall as it did in Europe and Asia especially. Therefore, this paper tries do unveil what’s behind this financial system and try to find ways to make it’s introduction in Brazil possible. In order to reach this, a qualitative research guided by the presentation of countries that have introduced Islamic finance, and interviews conducted with main players in Brazil linked to Islamic finance. The results of the research reflected partially the perspective of the academia, the expert, the Brazilian market and the Islamic finance industry, given that each interviewee represented one or more of these categories. This was completed with the overall conclusions drawn from the case studies presented, taking the main lessons form their experience. A coding system was developed to filter and organize the results. In terms of the opportunities Islamic finance has in Brazil, what stands out the most is the strong relation between Brazil and the Arab countries (adopters of Islamic finance), especially in exports, which represent situations in which Islamic finance could be adopted to intermediate the financing. The obstacles preventing this from happening are many, and are mainly linked to the unfamiliarity of the subject in the market and the delicate environment Brazil finds itself in, which is not favorable for new projects or investments. The Islamic finance procedures themselves are complicated and difficult, which makes the introduction process more complex. Given all that, there are many measures that can be taken already in order to incentive the introduction of Islamic finance in Brazil or even conduct some isolated Islamic finance operations. Murabahah is an example of a cost plus contract that can be used by exporters to sell their commodity abroad and sukuk is an alternative method for raising money with certificates backed by assets. These two operations can be adopted by Brazilian companies, however need to be conducted abroad due to regulatory complications. For the long term, having experts and professionals interested in Islamic finance ‘spreading the word’ and digging deeper into the subject in their workplace will open opportunities for the companies they work for and be an incentive for future adoption of Islamic finance by others. Entities also working towards the promotion of the halal (sharia-compliant) industries, which can be considered a fuel for Islamic finance, and tightening the relations between Brazil and the Arab countries, will help close the gap and familiarize both sides with the opportunities available.